Penyelesaian Non-Prosekutorial Dan Rekonsiliatif Terhadap Pelanggaran Hak Asasi Manusia Yang Berat - Ifdhal Kasim (Jurnal Hukum IUS QUIA IUSTUM, 2009)
Today, the Criminal Court Procedure is not the sole mechanism to put the responsibility for the serious violence against human rights. The Truth and Reconciliation Commission (KKR) which has been developed is considered to be another procedure to overcome national problems, and also is expected to respond individual injustice among the victims.Keywords: Human rights, reconsiliation, Rekonsiliasi, Truth and Reconciliation Commission